Polypyrrole conducting polymer and its application in removal of copper ions from aqueous solution - Hosseini, S.; Mahmud, N.H.M.E.; Yahya, R.B.; Ibrahim, F.; Djordjevic, I. (Elsevier, 2015)
Water-borne diseases are one of the major concerns in many countries. Particularly the presence of heavy metals inside the water resources can cause serious problems. In that perspective, current research is focused on the removal of copper (Cu2+) ions from aqueous solution by using polypyrrole. Synthesized polypyrrole before and after adsorption was analyzed by SEM equipped with EDX. The effect of important parameters on metal uptake has been investigated such as: dosage of the adsorbent, pH of the adsorption solution, contact time between adsorbent and contaminated water, and initial concentration of the copper ions. Furthermore, adsorption data corresponded well to the Langmuir isotherm model. Polypyrrole has proven to be an effective adsorbent that can be used not only for the removal of Cu2+ but also other heavy metal ions as well. (C) 2015 Elsevier B.V. All rights reserved.